Non-cognitive Characteristics of Gifted Students With Learning Disabilities: An In-depth Systematic Review - Beckmann, Else; Minnaert, Alexander (Frontiers in Psychology, 2018)
Gifted students who also have learning disabilities (G/LD) are often overlooked when students are assessed either for giftedness or specific learning disabilities. The cognitive and non-cognitive characteristics of these G/LD students are habitually discussed only briefly alongside identification and intervention issues and, beyond that, the relevance of non-cognitive characteristics is often left unconsidered. Accordingly, this study aims to conduct an in-depth review of the non-cognitive characteristics of these students for identification and intervention purposes. Detailed analysis was performed on 23 publications. High levels of negative emotions, low self-perception, and adverse interpersonal relationships, as well as high levels of motivation, coping skills and perseverance were found among these students. A common characteristic was a high degree of frustration with the academic situation. The study reveals that these students show considerably duality in their non-cognitive characteristics which requires tailored counseling skills to provide effective support for their learning needs.